PENGUATAN LITERASI MELALUI PEMANFAATAN APLIKASI LET’S READ DAN BUKU BACAAN CETAK DI SDN SUMBER - Nadhylla Nesty Sukma Wardani; Roken Sacti Udhiyanny; Charina Wahyu Meitika; Dewi Tryanasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading and writing literacy and digital literacy are basic competencies that need to be developed from elementary school level. Based on observations at SDN Sumber, Pangkur District, Ngawi Regency, it is known that students' interest in reading is still relatively low. This condition is caused by the limited availability of interesting reading materials and the suboptimal use of digital media in literacy activities. To overcome this problem, students from PGRI University Madiun's Community Service Program (KKN-T) group 32 implemented a community service program entitled “Happy Digital Literacy with Let’s Read .” This activity aimed to increase students' interest in reading and their ability to understand reading material through the integration of digital literacy using the Let’s Read application and the strengthening of printed reading materials in higher grades. The implementation method used a qualitative descriptive approach that included observation, coordination, media preparation, implementation, literacy reinforcement, evaluation, and reflection. The participants consisted of all students in grades I-VI, accompanied by teachers and KKN-T students as facilitators. The results of the activity showed that students were more enthusiastic during the reading process and were able to discuss the moral values of the stories. The use of digital media made reading activities in lower grades more interactive, while the addition of printed books to the reading corner increased reading intensity among students in higher grades. Overall, this program was effective in improving students' literacy skills and fostering a culture of sustainable literacy that supports the implementation of the Merdeka Curriculum in elementary schools.